Fabrication of Biocompatible Electro-conductive Silk Films with Natural Compounds for Tissue Engineering Applications. - Dimitrakakis, Nikolaos. (2017)
Abstract: In the present study electro conductive natural compounds are incorporated in silk based films, and the effects on film conductivity and dissolution are studied. Natural conducting compounds melanin and riboflavin were blended with silk to increase conductivity. Other compounds such as Fe(0) powder ferrofluid and NaCl solution also improved conductivity. Film properties and dissolution were studied for the different blends, and tuned using addition of glycerol and horseradish peroxidase cross-linking. Techniques such as electrospinning, doctor blade, spin coating, and paper-like film fabrication techniques were also explored to generate films with controlled dimensions and properties. The findings suggest that the incorporation of riboflavin along with NaCl and glycerol in silk films, along with water vapor annealing results in semiconductor films. More specifically, the two compositions of the films that exhibited highest conductivity contain 2 % w/v silk, 20 % w/v glycerol, 2 % w/v polyethylene oxide (PEO), 30 % v/v phosphate buffered saline (PBS) and 5 % w/v silk, 20 % w/v glycerol, 10 % w/v NaCl with conductivities of 5.72*10-2 S/m and 5.96*10-2 S/m at 20 °C. When silk is doped with riboflavin, NaCl, and glycerol, semiconducting behavior similar to drinking water conductivity is observed. Mass loss studies of the films included the immersion of the films for 7 days in 37° C in PBS. Film processing included samples that were heated for 2 hours in 60 °C immediately after casting, as well as those cured at room temperature. The results indicated that the heated samples provided the lowest mass loss of approximately 27 %. In conclusion, the present study demonstrates the correlation between composition and processing of silk films with their conductivity. These semiconductive films have the potential to be applied in tissue engineering applications such as nerve conduits, where conductivity plays an instrumental role in tissue restoration.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Biomedical Engineering.; Advisor: David Kaplan.; Committee: Tim Atherton, and Qiaobing Xu.; Keyword: Materials Science.